Clinical Presentation and Outcome of Ruptured Uterus in A Tertiary Hospital - Noor, Kazi Farhana; Yasmin, Farida; Biswas, Rupasree; Mumu, Moumita Tripura; Dev, Uma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Ruptured uterus is an obstetric emergency, carrying increased risk of maternal and perinatal mortality and morbidity especially in the developing countries. To determine the various aspects such as antecedent factors, clinical profile, management, outcome of ruptured uterus in a tertiary hospital. Methods: This prospective cross-sectional study conducted in the Department of Obstetrics and Gynecology in Chittagong Medical College Hospital, Chittagong, from January 2010 to December 2010. 70 consecutive admitted patients during this period was taken in this study. Results: During study period total 13635 obstetric patients were admitted and among them 70 cases were of ruptured uterus which gives an incidence of 0.5%. 92.85% of the women were multiparous. 77% patient did not have any antenatal care. 81% were illiterate and 82% belong to low socio-economic class. Common risk factors were mal-handling of labor by untrained dai (44%) cephalopelvic disproportion (35%) previous caesarean scar (34.28%) shoulder presentation 15%, abused of oxytocic drug (14%). Shock and sepsis were the prominent presenting features. In most cases, the tear was in the lower segment and in 54 patients (80%) the tear was complete. 25 (37%) patients had sub-total hysterectomy, 22 had repair and 13 (19.4%) had total hysterectomy. Maternal and fetal mortality rate was 11.42% and 88.5% respectively. Conclusion: A high incidence (1 in 195) of ruptured uterus mainly because of inadequate natal and intranatal care, high parity, mismanagement of labor, Low socio-economic condition and illiteracy. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 29-33